Changes in preoperative anxiety after leaflet- and video-based education among patients undergoing laparoscopic cholecystectomy - Nurdiansyah Nurdiansyah; Tutik Rahayu; Hernandia Distinarista (JOURNAL OF Medical Surgical Concerns, 2026)
Background: Preoperative anxiety may affect patients’ psychological readiness and perioperative recovery. Structured education using accessible written and audiovisual media may help patients understand the surgical process and reduce uncertainty before laparoscopic cholecystectomy. Purpose: To examine changes in preoperative anxiety after leaflet- and video-based education among patients undergoing laparoscopic cholecystectomy. Method: This quasi-experimental study used a one-group pretest–posttest design involving 38 patients at Sari Asih Ciledug Hospital, Tangerang, Indonesia. Participants received a 20-minute educational session using a leaflet and video. Anxiety was assessed before and after the intervention using the Amsterdam Preoperative Anxiety and Information Scale. Pretest and posttest results were compared using the Wilcoxon signed-rank test. Results: Before education, 18 participants (47.4%) had mild anxiety, 12 (31.6%) had moderate anxiety, 3 (7.9%) had severe anxiety, and 5 (13.2%) had no anxiety. After education, 22 participants (57.9%) had no anxiety, 13 (34.2%) had mild anxiety, 2 (5.3%) had moderate anxiety, and 1 (2.6%) had severe anxiety. Anxiety levels differed significantly between the pretest and posttest assessments (p < 0.001).